Informational asymmetries in laboratory asset markets with state-dependent fundamentals - Claudia Keser; Andreas Markstädter (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
We investigate the formation of market prices in a new experimental setting involving multi-period call-auction asset markets with state-dependent fundamentals. We are particularly interested in two informational aspects: (1) the role of traders who are informed about the true state and/or (2) the impact of the provision of Bayesian updates of the assets state-dependent fundamental values (BFVs) to all traders. We find that markets with asymmetrically informed traders exhibit smaller price deviations from fundamentals than markets without informed traders. The provision of BFVs has little to no effect. Behavior of informed and uninformed traders differs in early periods but converges over time. On average, uninformed traders offer lower "higher" limit prices and hold less "more" assets than informed traders in "good"-state ("bad"-state) markets. Informed traders earn superior profits. The precision of mar ket price forecasts is impeded by the presence of insiders.
Keywords: C92; D47; D53; D82; G14; 330; experimental economics; asset markets; informational asymmetries